Study of the properties of drill cuttings at their use as technogenic raw materials for the production of building ceramics - Rykusova, Nadegda; Shestopalov, Oleksii; Shchukina, Liudmyla; Briankin, Oleksandr; Galushka, Yaroslav (Scientific Route OÜ, Estonia, 2020)
The possibility of utilizing drill cuttings in the technology of building ceramics is investigated. Using the microscopic and X-ray spectral methods of analysis, the chemical and mineral composition and radiological properties of two samples of drill cuttings – waste gas drilling in the Poltava region – are determined. Using the bioindication method, it is established that the studied drill cuttings are phytotoxic and harm the environment, therefore, they need to be disposed of. According to the radioactivity, the cuttings are investigated, they belong to the materials of the 1st class, which allows using them without restrictions in the construction and production of building materials. The main ceramic-technological characteristics of the cuttings are determined. It is established that one of the cuttings in its composition is pre-burning and burning properties similar to clay rocks, the second cutting is unsintered psammite-aleuropelite material with a high content of calcium and magnesium carbonates, quartz and feldspar. The fundamental possibility of using the studied drill cuttings as the main raw material and mineral additives in the compositions of the masses to obtain wall ceramics with the necessary consumer properties is established.
Keywords: drilling; drill cuttings; ceramic products; environmental pollution; biotesting; raw materials; mineral and chemical composition; particle size distribution; sintering